Elevated matrix metalloproteinase concentrations offer novel insight into their role in pediatric tuberculous meningitis - Li, YJ; Wilkinson, KA; Wilkinson, RJ; Figaji, AA; Rohlwink, UK (Oxford University Press, 2019)
We collected lumbar and ventricular cerebrospinal fluid and serum from 40 children treated for tuberculous meningitis and measured the concentrations of gelatinases and their inhibitors. The concentrations of matrix metalloproteinase 9 (MMP-9), MMP-2, tissue inhibitor of metalloproteinase 1 (TIMP-1), and TIMP-2 were significantly elevated in the lumbar CSF samples, and we found interesting dynamics for MMP-9 that offer novel insight into its role in pediatric patients with tuberculous meningitis.